007 Immunotherapy responsive neuropathic pain associated with LGI1 and CASPR2 antibodies. (23rd August 2021) - Ramanathan, Sudarshini; Davies, Alexander; Uy, Christopher; Tseng, Mandy; Paneva, Sofija; Michael, Sophia; Varley, James; Binks, Sophie; Themistocleous, Andreas; Anziska, Yaacov; Candalija, Ana; Soni, Anushka; et al.
Abstract : Objective: We evaluated pain in leucine-rich glioma inactivated1(LGI1) and contactin-associated protein2(CASPR2)-antibody positive(Ab+) patients, to evaluate clinical associations and pathophysiology of treatable pain syndromes. Methods: 108 LGI-Ab+, 33 CASPR2-Ab+, and 6 LGI1/CASPR-Ab+patients were phenotyped. Pain questionnaires were undertaken to identify neuropathic pain using the Douleur Neuropathique(DN4), patient reported outcome measurement information system(PROMIS), and quality of life(EQ5D). Skin biopsies, and serum binding to cell-based assays, sensory neuronal cocultures, and dorsal root ganglion(DRG) cultures were undertaken. Results: 39/147 patients described pain, including 17/33 CASPR2-Ab+(52%), 20/108 LGI1-Ab+(19%), and 2 LGI/CASPR2-Ab+patients. Questionnaires completed in 23/39(59%) revealed comparable DN4 scores(p=0.319) with 58% of LGI1-Ab+ and 67% of CASPR2-Ab+patients having neuropathic pain. Patients rated >50% response in 8/30(27%) analgesia trials, versus 20/40(55%) immunotherapy trials(p=0.045). PROMIS ratings were similar between LGI1-Ab+ and CASPR2-Ab+patients at nadir(p=0.662), but showed more improvement following immunotherapy in LGI1-Ab+(p=0.008) than CASPR2-Ab+patients(p=0.125). At follow-up(median 57 months) CASPR2-Ab+patients showed more impairment in mobility(p=0.014), daily activities(p=0.019), and anxiety/depression(p=0.043); and lower overall health(p=0.019) on the EQ5D compared to LGI1-Ab+patients. Intraepidermal nerve fibre density was reduced in 2 LGI1-Ab+ and 1 CASPR2-Ab+patients. Serum immunoglobulin G(IgG) from 6/16 CASPR2-Ab+patients bound to sensory neuronal cocultures compared to 0/14 LGI1-Ab+patients(p=0.019) and 0/12 healthy controls. Serum IgG from 10/16 CASPR2-Ab+patients bound to DRG cultures compared to 1/14 LGI1-Ab+patients(p=0.0024) and 1/12 healthy controls. Conclusion: Neuropathic pain may be present in both LGI-Ab+ and CASPR2-Ab+patients, and is immunotherapy responsive. Serum IgG from CASPR2-Ab+patients more frequently bound sensory neurons and dorsal root ganglia, suggesting pathophysiological differences which may underlie the more severe pain in these patients.